Cost‐effectiveness of quantitative hepatitis B virus surface antigen testing in pregnancy in predicting vertical transmission risk. (13th May 2016) - Samadi Kochaksaraei, Golasa; Congly, Stephen E.; Matwiy, Trudy; Castillo, Eliana; Martin, Steven R.; Charlton, Carmen L.; Coffin, Carla S.
Abstract: Background & Aims: Vertical transmission of hepatitis B virus (HBV) can occur despite immunoprophylaxis in mothers with high HBV DNA levels (>5–7 log10 IU/ml). Quantitative hepatitis B surface antigen (qHBsAg) testing could be used as a surrogate marker to identify high viral load carriers, but there is limited data in pregnancy. We conducted a prospective observational study to determine the cost‐effectiveness and utility of qHBsAg as a valid surrogate marker of HBV DNA. Methods: Pregnant patients with chronic hepatitis B were recruited from a tertiary referral centre. HBV DNA levels and qHBsAg were assessed in the second to third trimester. Statistical analysis was performed by Spearman's rank correlation and student's t ‐test. The cost‐effectiveness of qHBsAg as compared to HBV DNA testing was calculated. Results: Ninety nine women with 103 pregnancies, median age 32 years, 65% Asian, 23% African and 12% other [Hispanic, Caucasian] were enrolled. Overall, 23% (23/99) were HBV e Ag (HBeAg)‐positive. A significant correlation between qHBsAg and HBV DNA levels was noted in HBeAg‐positive patients ( r = 0.79, P < 0.05) but not in HBeAg‐negative patients ( r = 0.17, P = 0.06). In receiver operating characteristic analysis, the optimal qHBsAg cut‐off values for predicting maternal viraemia associated with immunoprophylaxis failure (i.e., HBV DNA ≥7 log10 IU/ml) was 4.3 log10 IU/ml (accuracy 98.7%, sensitivity 94.7%, specificity 94.4%) (95% CI, 97–100%, P < 0.05). Use of HBV DNA as compared to qHBsAg costs approximately 20 000 more per infection prevented. Conclusion: In resource poor regions, qHBsAg could be used as a more cost‐effective marker for high maternal viraemia, and indicate when anti‐HBV nucleos/tide analogue therapy should be used to prevent HBV immunoprophylaxis failure.